Primary coronary angioplasty in 9,434 patients during acute myocardial infarction: predictors of major in- hospital adverse events from 1996 to 2000 in Brazil - Mattos,Luiz Alberto (2002)
OBJECTIVE: To verify the results after the performance of primary coronary angioplasty in Brazil in the last 4 years. METHODS: During the first 24 hours of acute myocardial infarction onset, 9,434 (12.2%) patients underwent primary PTCA. We analyzed the success and occurrence of major in-hospital events, comparing them over the 4-year period. RESULTS: Primary PTCA use increased compared with that of all percutaneous interventions (1996=10.6% vs. 2000=13.1%; p<0.001). Coronary stent implantation increased (1996=20% vs. 2000=71.9%; p<0.001). Success was greater (1998=89.5% vs. 1999=92.5%; p<0.001). Reinfarction decreased (1998=3.9% vs. 99=2.4% vs. 2000=1.5%; p<0.001) as did emergency bypass surgery (1996=0.5% vs. 2000=0.2%; p=0.01). In-hospital deaths remained unchanged (1996=5.7% vs. 2000=5.1%, p=0.53). Balloon PTCA was one of the independent predictors of a higher rate of unsuccessful procedures (odds ratio 12.01 [CI=95%] 1.58-22.94), and stent implantation of lower mortality rates (odds ratio 4.62 [CI=95%] 3.19-6.08). CONCLUSION: The success rate has become progressively higher with a significant reduction in reinfarction and urgent bypass surgery, but in-hospital death remains nearly unchanged. Coronary stenting was a predictor of a lower death rate, and balloon PTCA was associated with greater procedural failure.